Toward a "Theoretical Toolbox" for the Supplier‐Enabled Fuzzy Front End of the New Product Development Process. Issue 1 (6th August 2015) - Wowak, Kaitlin D.; Craighead, Christopher W.; Ketchen, David J.; Hult, G. Tomas M.
Abstract : As technology life cycles have shortened in both products and processes, more research attention has been placed on the involvement of suppliers within the new product development (NPD) process. The majority of this research focuses on the execution‐oriented back‐end (production through product launch) resulting in a dearth of research centered on the fuzzy front end (FFE; idea generation through a production‐ready product). This is surprising considering that the FFE is arguably the most important and challenging phase in the NPD process coupled with how critical suppliers may be to this phase of NPD. To provide a foundation for future inquiry in this important, but underdeveloped, research area, we describe how five promising theories can help inform future research centered on how suppliers can enhance the FFE of the NPD process. Specifically, we use: (1) resource orchestration theory; (2) real options theory; (3) tournament theory; (4) attribution theory; and (5) justice theory to help make the FFE of the NPD process become less "fuzzy" and more concrete.